Pelaksanaan program Inpres desa tertinggal dalam perspektif pembangunan pedesaan - Unggul Priyadi (Universitas Islam Indonesia, 1997)
In 1993 Indonesian overnment launched first IDT (Inpres Desa Tertinggal) program. IDT program is more than government effort to eliminate poverty, but a rural development strategy. It is directed to hike economic autonomy and to accelerate growth by increasing social economic activity based on decentralization principles.